Induction of systemic lupus erythematosus syndrome in BALB/c mice by immunization with active chromatin - LI Hong; ZHANG Yun-yi; SUN Ya-nan; HUANG Xi-yi; JIA Yong-feng; LI Duan (Acta Pharmacologica Sinica, 2016)
AIM: To establish an animal model for systemic lupus erythematosus (SLE)-like syndrome in mice. METHODS: BALB/c mice were immunized with active chromatin isolated from ConA-activated syngeneic spleno-lymphocytes. Plasma samples of mice were tested by enzyme-linked immunosorbent assays (ELISA) for the presence of IgG anti-dsDNA, -ssDNA, and anti-histone antibodies. Tumor necrosis factor-alpha (TNF-alpha) in serum was measured by ELISA. Spleno-lymphocyte proliferation assays and the levels of interferon-gamma (IFN-gamma) in supernatants were tested respectively. Proteinuria was measured. Kidneys were examined by direct immunohistochemical method and light microscopy. RESULTS: Anti-ds DNA, ssDNA, and histone antibodies were induced in active chromatin-immunized mice, the proliferation response of splenocytes to ConA and LPS were reduced, levels of interferon-gamma in supernatants and TNF-alpha in serum were lowered. Lupus nephritis was assessed by the presence of Ig deposits, glomerular pathology and proteinuria. CONCLUSION: The active chromatin-induced SLE-like mouse model was similar to idiopathic SLE in human.